(untitled) (Bangladesh Journal of Zoology, 2021)
The research work was conducted for isolation and identification of potential pathogenic bacteria from blow fly (Calliphora spp.) and to investigate their antibiotic susceptibility. For this purpose, 20 blow flies were collected from 4 selected areas (Curzon Hall, Dhaka Medical College Hospital, Fruit Store and Fish Market) of Dhaka city. A total of 40 samples (20 from external surface and 20 from alimentary gut homogenates) were prepared from the blow flies. Among the total 20 flies, 3(15%) were collected from Curzon Hall and 5(12.5%) isolates were obtained from them; 6(30%) flies were collected from DMCH which had 11(27.5%) isolates; 5(25%) flies were collected from fruit stores and 10(25%) isolates were collected from there; 6(30%) flies were collected from fish market and 14(35%) isolates were collected from there. The isolated bacteria were presumptively identified as Escherichia coli, 12 (30%); Salmonella spp., 8 (20%); Shigella spp., 4(10%); Enterobacter spp., 3 (7.5%); Klebsiella spp., 2 (5%); Bacillus spp., 7 (17.5%) and Staphylococcus spp., 4 (10%) in number which were based on morphology as observed under microscope as well as cultural and biochemical properties. All of these isolates were resistant to various antibiotics. Bacterial susceptibility showed that E. coli isolates were highly resistant (66.6%) to Penicillin, Salmonella spp. mostly resistant (62.5%) to Penicillin and Tetracycline. Klebsiella spp. Isolates were 100% resistant to Penicillin and 100% sensitive to Ciprofloxacin, Imipenem and Tetracycline. In case of Shigella spp. and Enterobacter spp., 75% and 100% isolates were resistant to Penicillin respectively. Among the Staphylococcus spp. isolates, 75% were resistant to Ampicillin and Penicillin. In case of Bacillus spp. isolates, 57.2% were resistant to Penicillin and 100% sensitive to Imipenem. Antibiotic resistance of these species affect our human health also. This study demonstrated the potential of blow flies as a vector of various pathogenic microorganisms and a mode of transmission of antibiotic resistance. Bangladesh J. Zool. 49 (2): 205-214, 2021